Preparing for and reimagining education of the future: towards a new norm of learning in the post pandemic stage - Hamawiya, Adham; Hussien, Suhailah (IIUM Press, 2022)
The release of this month’s issue of the International Islamic University Malaysia Journal of Educational Studies (IJES) coincides with the university’s return to face-to-face education in the post-pandemic (Covid-19) stage after two years of remote education via online. In our attempt to adjust and return to the previous norm of learning, this issue presents a range of studies that introduce alternative pedagogies to improve learning and attempt to provide a more equitable education for the marginalized group of the society. The International Commission on the Future of Education at the United Nations Educational, Scientific, and Cultural Organization (UNESCO) 2020 report entitled “Education in a post-Covid world: Nine ideas for public action”, calls for teachers and educational leaders be given autonomy and flexibility to collaborate with students, the community, and other stakeholders